Unsuspected rupture in unscarred uterus at an early gestation: a clinical dilemma - Singh, Neeta; Kulshrestha, Vidushi; Dhiman, Soniya; Kaur, Tarang Preet; Meena, Jyoti; Mathur, Sandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Spontaneous uterine rupture in early second trimester is extremely rare specially in absence of predisposing factors. A pregnant patient presented at 15 weeks’ gestation with lower abdominal pain and vomiting since two days. Ultrasound findings and deranged liver function tests reinforced the diagnosis of chronic liver disease with pregnancy. Clinical course a day later raised suspicion of ruptured uterus and patient was immediately taken for laparotomy. Intra-operatively, hemoperitoneum and 4 cm fundus rent was found. Total hysterectomy was performed and histopathology revealed placenta percreta as the probable cause of spontaneous rupture. The case highlights that a high index of clinical suspicion, an attentive daily clinical examination and immediate surgical management can avert life-threatening catastrophe.